2022
DOI: 10.1093/mnras/stac1134
|View full text |Cite
|
Sign up to set email alerts
|

Stellar populations of a sample of far-infrared AGN and non-AGN green valley galaxies

Abstract: We present a study on the stellar populations and stellar ages of a subsample of far-infrared (FIR) active galactic nucleus (AGN) and non-AGN green valley galaxies at ${0.6\, \lt \, z\, \lt \, 1.0}$ using the data from the Cosmological Evolution Survey field. We used long-slit spectroscopy and derived stellar populations and stellar ages using the stellar population synthesis code ‘starlight’ and analysed the available Lick/IDS indices, such as Dn4000 and HδA. We find that both FIR AGN and non-AGN green valley… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 168 publications
3
2
0
Order By: Relevance
“…Finally, we note that the three unambiguous cases of outflows in the FIR AGN green valley galaxies are situated within, or just at the border, of the MS of starforming galaxies. This suggests the possibility that we are witnessing the influence of the AGNs on their host galaxies in this sample (such as possible positive feedback), in line with results we have reported previously in Mahoro et al (2017Mahoro et al ( , 2019Mahoro et al ( , 2022. Nevertheless, we consider this a preliminary result, and plan further observations of larger samples, and using data obtained with a new generation of telescopes, including other wavelengths and with higher spatial resolution (e.g., JWST/NIRSpec or the Atacama Large Millimeter/ submillimeter Array).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, we note that the three unambiguous cases of outflows in the FIR AGN green valley galaxies are situated within, or just at the border, of the MS of starforming galaxies. This suggests the possibility that we are witnessing the influence of the AGNs on their host galaxies in this sample (such as possible positive feedback), in line with results we have reported previously in Mahoro et al (2017Mahoro et al ( , 2019Mahoro et al ( , 2022. Nevertheless, we consider this a preliminary result, and plan further observations of larger samples, and using data obtained with a new generation of telescopes, including other wavelengths and with higher spatial resolution (e.g., JWST/NIRSpec or the Atacama Large Millimeter/ submillimeter Array).…”
Section: Discussionsupporting
confidence: 91%
“…This particular result in this paper, based on the study of the [O III] λ5007 emission line profiles of a small sample of optically selected green valley AGNs with FIR emission, is thus very much in line with that obtained using photometric techniques of statistical samples in Mahoro et al (2017Mahoro et al ( , 2019Mahoro et al ( , 2022, where we suggested the possibility of ongoing positive AGN feedback in FIR green valley galaxies. It will be interesting to distinguish further whether we indeed are witnessing positive feedback by the AGNs on the star formation activities of the host galaxies, or, for example, whether any star formation quenching has not yet started in these galaxies, and if so, why, and what the exact physical role of gas outflows is.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…L  , older than any dwarf sample. In Mahoro et al (2022), however, 77% of the 17 X-ray selected, far-IR detected AGN-host galaxies have á ñ < t log 9…”
Section: Mean Stellar Agementioning
confidence: 99%
“…Shin et al (2019) reported a positive feedback scenario in NGC 5728, due to higher SFRs in the encountering region where the ionized gas outflows encounter the star formation ring at 1 kpc radius. Mahoro et al (2022) showed that there are no apparent signs of negative AGN feedback, after comparing host galaxy properties of far-infrared AGN and non-AGN green valley galaxies. Therefore, it is interesting to provide further clues on the contradictory effects of AGN feedback on star formations, through different methods, which is the main objective of this manuscript.…”
Section: Introductionmentioning
confidence: 99%